Cyborg insect: walking control - Koh, Jun Yuan (Nanyang Technological University, 2024)
Cyborg insects have been extensively researched as an alternative to miniature robots for use in search and rescue operations post-natural disasters due to its energy efficiency and operational longevity. The Madagascar Hissing Cockroach is widely utilised as the base insect for its climbing prowess and high load capacity. This project aims to design a flotation device that will enable existing land bound cockroaches to traverse on water. The flotation device utilises a Madagascar Hissing Cockroach equipped with pre-existing technology to provide locomotion. Adequate spaces were designed to enable the addition of other tools of image capturing in the future. The device maneuverability was subsequently tested. The results showed that the device is workable and recommendations for future improvements to increase autonomy have been documented in this paper.